Impact of liquidity on capital structure and financial performance of non-financial-listed companies in the vietnam stock market - Nguyen Hoang Phi Nam; Tran Thi My Tuyen (Future Business Journal)
Abstract The primary objective of this study is to conduct a comprehensive analysis of the relationships between liquidity (LIQ), capital structure (LEV), and financial performance (FIP). Additionally, we seek to investigate the indirect effect of liquidity (LIQ) on financial performance (FIP) by examining the intermediary role of the capital structure (LEV) of non-financial-listed companies in the Vietnamese stock market. This study utilizes PLS-SEM with a robust sample of 644 non-financial-listed companies in the Vietnamese stock market. The findings suggest that liquidity positively influences financial performance but negatively impacts capital structure. Conversely, capital structure negatively affects financial performance. Thus, liquidity indirectly enhances financial performance through capital structure mediation. This research result can provide suggestions for non-financial enterprises in making financial decisions to increase financial efficiency by increasing the holdings of highly liquid assets to prevent risks and take advantage of new investment opportunities in the future. In addition, increasing the holding of highly liquid assets also reduces debt pressure and reduces interest costs, thereby increasing financial efficiency. Our research shows that the relationship between economic factors is extremely complex; specifically, our research shows the true nature of the positive impact of liquidity on financial performance, including direct positive effects and indirect positive effects through capital structure. In addition, our research results also show that non-financial enterprises that want to increase financial efficiency need to pay attention to revenue growth, and non-financial companies with larger total assets (size) will have more advantages in increasing financial performance.